PROSPECTS OF MANAGEMENT ACCOUNTING AND COST CALCULATION - Marian ŢAICU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Progress in improving production technology requires appropriate measures to achieve an efficient management of costs. This raises the need for continuous improvement of management accounting and cost calculation. Accounting information in general, and management accounting information in particular, have gained importance in the current economic conditions, which are characterized by risk and uncertainty. The future development of management accounting and cost calculation is essential to meet the information needs of management.